The Role of 3 Tesla Diffusion-Weighted Imaging in the Differential Diagnosis of Benign versus Malignant Cervical Lymph Nodes in Patients with Head and Neck Squamous Cell Carcinoma. (9th June 2014) - Barchetti, Flavio; Pranno, Nicola; Giraldi, Guglielmo; Sartori, Alessandro; Gigli, Silvia; Barchetti, Giovanni; Lo Mele, Luigi; Marsella, Luigi Tonino
Abstract : Objective . The aim of this study was to validate the role of diffusion-weighted imaging (DWI) at 3 Tesla in the differential diagnosis between benign and malignant laterocervical lymph nodes in patients with head and neck squamous cell carcinoma (HNSCC). Materials and Methods . Before undergoing surgery, 80 patients, with biopsy proven HNSCC, underwent a magnetic resonance exam. Sensitivity (Se) and specificity (Spe) of conventional criteria and DWI in detecting laterocervical lymph node metastases were calculated. Histological results from neck dissection were used as standard of reference. Results . In the 239 histologically proven metastatic lymphadenopathies, the mean apparent diffusion coefficient (ADC) value was 0.903 × 10 −3  mm 2 /sec. In the 412 pathologically confirmed benign lymph nodes, an average ADC value of 1.650 × 10 −3  mm 2 /sec was found. For differentiating between benign versus metastatic lymph nodes, DWI showed Se of 97% and Spe of 93%, whereas morphological criteria displayed Se of 61% and Spe of 98%. DWI showed an area under the ROC curve (AUC) of 0.964, while morphological criteria displayed an AUC of 0.715. Conclusions . In a DWI negative neck for malignant lymph nodes, the planned dissection could be converted to a wait-and-scan policy, whereas DWI positive neck would support the decision to perform a neck dissection.